Seismic Shot Point Navigation Data from the Western North Atlantic Ocean acquired during the R/V Robert D. Conrad expedition RC1903 (1975) ... - Ewing, John (Interdisciplinary Earth Data Alliance (IEDA), 2007)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Robert D. Conrad expedition RC1903 conducted in 1975 (Chief Scientist: Dr. John Ewing). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Funding was provided by NSF grant: DES75-15865. ...